{4,4′-Dimethyl-2,2′-[2,2-dimethylpropane-1,3-diylbis(nitrilomethanylylidene)]diphenolato}copper(II) monohydrate - Hadi Kargar; Reza Kia; Fatemeh Ganji; Valiollah Mirkhani (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, [Cu(C21H24N2O2)]·H2O, comprises half of a Schiff base complex and half of a water molecule. The whole compound is generated by crystallographic twofold rotation symmetry. The geometry around the CuII atom, located on a twofold axis, is distorted square-planar, which is supported by the N2O2 donor atoms of the coordinating Schiff base ligand. The dihedral angle between the symmetry-related benzene rings is 47.5 (4)°. In the crystal, the water molecule that is hydrogen bonded to the coordinated O atoms links the molecules via O—H...O interactions into chains parallel to [001]. The crystal structure is further stabilized by C—H...π interactions, and by π–π interactions involving inversion-related chelate rings [centroid–centroid distance = 3.480 (4) Å].